2021
DOI: 10.3390/bios11060188
|View full text |Cite
|
Sign up to set email alerts
|

Integrating ECG Monitoring and Classification via IoT and Deep Neural Networks

Abstract: Anesthesia assessment is most important during surgery. Anesthesiologists use electrocardiogram (ECG) signals to assess the patient’s condition and give appropriate medications. However, it is not easy to interpret the ECG signals. Even physicians with more than 10 years of clinical experience may still misjudge. Therefore, this study uses convolutional neural networks to classify ECG image types to assist in anesthesia assessment. The research uses Internet of Things (IoT) technology to develop ECG signal mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The convolutional neural network is used to classify the images to aid in anesthesia. During the research, three models, ResNet, SqueezeNet, and AlexNet, used and showed the accuracy and waveform as 0.97, 0.75, and 0.96, respectively [ 7 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The convolutional neural network is used to classify the images to aid in anesthesia. During the research, three models, ResNet, SqueezeNet, and AlexNet, used and showed the accuracy and waveform as 0.97, 0.75, and 0.96, respectively [ 7 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A health monitoring system based on deep learning in the IoT context[ 23 ] is also developed to predict CVD. Similarly, Yeh et al [ 24 ] have used deep neural networks to analyze ECG signals to assess the patient's condition and give appropriate drugs. The deep learning approach is also used in the IoT[ 25 ] for valvular heart disease screening.…”
Section: System Development Preliminariesmentioning
confidence: 99%
“…Based on the World Health Organization (WHO) report, 30–40% of deaths in the entire world are due to cardiovascular diseases which is an alarming situation, and the ratio is increasing with the passage of time. This irregular functioning and abnormalities can be found by cardiologists [ 1 ]. Literature indicates that it is difficult to identify the accurate position and transition of ECG signals with one or a simple algorithm.…”
Section: Introductionmentioning
confidence: 99%